Morphotaxonomic revision of species-groups of Simulium (Simulium) (Diptera: Simuliidae) in the Oriental Region - Takaoka, Hiroyuki (Zootaxa, 2017)
Species of eight species-groups (seven named and one unnamed) of Simulium (Simulium) Latreille are revised chiefly based on the adult female and male genitalia. Four species-groups are each divided into more than two groups. Thus, the S. christophersi species-group is divided into two (S. christophersi and S. nebulicola species-groups), the S. griseifrons species-group into six (S. griseifrons, S. grossifilum, S. chungi, S. crocinum, S. indicum and S. yadongense species-groups), the S. malyschevi species-group into two (S. malyschevi and S. pavlovskii species-groups), and the S. melanopus species-group into three (S. melanopus, S. dumogaense and S. iridescens species-groups). The S. crassifilum species-group is merged with the S. variegatum species-group. Simulium fulvipes (Ono) of the former S. malyschevi species-group and S. dentastylum Yang, Chen & Luo of Simulium s. str. species unplaced to species-group are removed from the subgenus Simulium because their male styles are subequal in length to the coxites. A revised classification of species of the 15 species-groups including eight new species-groups of Simulium (Simulium) is presented. Keys to 20 species-groups of Simulium (Simulium) in the Oriental Region are provided for adult females and males.